2017
DOI: 10.1063/1.4998284
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-induced strain and charge doping in CVD-grown monolayer MoS2

Abstract: Due to its electronic-grade quality and potential for scalability, two-dimensional (2D) MoS2 synthesized by chemical vapor deposition (CVD) has been widely explored for electronic/optoelectronic applications. As 2D MoS2 can be considered a 100% surface, its unique intrinsic properties are inevitably altered by the substrate upon which it is grown. However, systematic studies of substrate-layer interactions in CVD-grown MoS2 are lacking. In this study, we have analyzed built-in strain and charge doping using Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
231
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(252 citation statements)
references
References 38 publications
21
231
0
Order By: Relevance
“…In addition, we noticed a faint continuous background emission and it was subtracted during further analysis. All PL bands are red‐shifted with respect to peak positions of high quality exfoliated monolayers and this is typical for CVD grown strained MoS 2 on SiO 2 /Si substrates . At the same time, we did not observe any features corresponding to indirect transition usually visible in multilayers at about 1.5 eV .…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…In addition, we noticed a faint continuous background emission and it was subtracted during further analysis. All PL bands are red‐shifted with respect to peak positions of high quality exfoliated monolayers and this is typical for CVD grown strained MoS 2 on SiO 2 /Si substrates . At the same time, we did not observe any features corresponding to indirect transition usually visible in multilayers at about 1.5 eV .…”
Section: Resultssupporting
confidence: 65%
“…As it was shown in refs. , the reduced electron concentration leads to a blue shift of the A1 peak compared with the peak position in exfoliated high quality monolayer. It was also shown that the nitrogen doping could be an effective way to produce hole doping in MoS 2 monolayers by creating N S acceptor defects.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations